Enhancing immune response, antioxidant capacity, and gut health in growing beagles through a chitooligosaccharide diet - Cheng, Guoqiang; Hu, Tingting; Zeng, Yu; Yan, Liangchun; Liu, Yanglu; Wang, Yongjin; Xia, JieYing; Dong, Han; Chen, Dong; Cheng, Tingting; Peng, Guangneng; Zhang, Li (Frontiers in Veterinary Science, 2024)
Chitooligosaccharides (COS) have attracted significant attention due to their unique biological activities, water solubility, and absorbable properties. The objective of the present study was to investigate the impact of COS-supplemented diets on the immune response, antioxidative capacity, hematology, serum biochemistry, and modulation of intestinal microbiota in growing beagles. Twelve weaning male beagles (6 weeks old; weighing 3.6 ± 0.6 kg) were fed either a control diet (food without COS, n = 6) or a COS-supplemented diet (n = 6) twice daily for 7 weeks. Blood samples collected at weeks 4 and 7 indicated that hematology and serum biochemistry remained unaffected by COS supplementation. Compared with the control group, the test group showed higher levels of serum antibodies against the canine distemper virus and parvovirus, higher levels of immunoglobulin A, G, and M, and increased activities of superoxide dismutase, glutathione peroxidase, and catalase. In addition, COS was observed to modulate the intestinal flora by enhancing the presence of probiotics, such as Muribaculaceae, Prevotellaceae_Ga6A1_group, Lactobacillus, Collinsella, Blautia, and Lachnospiraceae_NK4A136_group. In summary, a COS-supplemented diet could effectively improve dog health by regulating immune function and antioxidant responses and modulating intestinal microbiota. This study highlights the potentiality of using COS as a valuable nutraceutical for growing dogs.